ANALISIS EFISIENSI INDUSTRI ROKOK DI INDONESIA DENGAN MENGGUNAKAN METODE DEA (DATA ENVELOPMENT ANALYSIS) TAHUN 2006 - 2008 - Ida Ayu Puspitasari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
This study aims to determine the efficiency levels of cigarettes industry inIndonesia. The analysis tools used in this study is the DEA (Data Envelopment Analysis)method of analysis. Expecially for the “Go Public” firms those are PT BAT Indonesia, PT Bentoel, PT Gudang Garam, PT HM Sampoerna. The research, used secondary data, from the Indonesian Capital Market Directory year 2006 - 2008. Variables used in the study consist of four input variables and two output variables. Its input variables consist of labor, Debt, Capital, and Total Asset, whiles its output variable consist of Net Sales and Gross Profit. The research results show that there only two companies that consistent to maintained the level of efficiency of 100% during the study, namely PT BAT Indonesia and PT HM Sampoerna. Meanwhile, two other companies show their performance levels efficiency have not stabillized during the study, namely PT Bentoel and PT Gudang Garam.Keywords : Efficiency, DEA, Cigarette Company, Labor, Debt, Capital, Total Asset, Net Sales, Gross Profit.